Differential effect of phosphatidylethanolamine depletion on raft proteins: further evidence for diversity of rafts in Saccharomyces cerevisiae - Opekarová, Miroslava; Malínská, Katerina; Nováková, Linda; Tanner, Widmar (Biochimica et biophysica acta, 2005)
A considerable amount of evidence supports the idea that lipid rafts are involved in many cellular processes, including protein sorting and trafficking. We show that, in this process, also a non-raft lipid, phosphatidylethanolamine (PE), has an indispensable function. The depletion of this phospholipid results in an accumulation of a typical raft-resident, the arginine transporter Can1p, in the membranes of Golgi, while the trafficking of another plasma membrane transporter, Pma1p, is interrupted at the level of the ER. Both these transporters associate with a Triton (TX-100) resistant membrane fraction before their intracellular transport is arrested in the respective organelles. The Can1p undelivered to the plasma membrane is fully active when reconstituted to a PE-containing vesicle system in vitro. We further demonstrate that, in addition to the TX-100 resistance at 4 degrees C, Can1p and Pma1pa exhibit different accessibility to nonyl glucoside (NG), which points to distinct intimate lipid surroundings of these two proteins. Also, at 20 degrees C, these two proteins are extracted by TX-100 differentially. The features above suggest that Pma1p and Can1p are associated with different compartments. This is independently supported by the observations made by confocal microscopy. In addition we show that PE is involved in the stability of Can1p-raft association.
Keywords: transportní systémy pro bazické aminokyseliny; membránové mikrodomény; Saccharomyces cerevisiae; fosfatidylethanolaminy; membránové proteiny; Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae Proteins; Membrane Proteins; Protein Folding; Amino Acid Transport Systems, Basic; protonové ATPasy; sbalování proteinů; Detergents; Membrane Microdomains; Proton-Translocating ATPases; Phosphatidylethanolamines; detergenty